The Impact of Expansionary Policies on the Global Trade Balance and Trade Openness: An Empirical Study on a Group of European Union Countries - Sahar Kareem Gatae Ali (Journal of Regional Economics and Development, 2026)
The research aims to analysis impact Policies expansion, whether Cash or Finance, on balance commerce Global and indicator openness Commercial in group from countries Union European, Which is: Germany, France, Italy, Spain, And the Netherlands, during period Extended From 2015 to 2024. It begins Search from hypothesis Its meaning that Policies expansion, via Its tools different like cut Prices Interest, more Spending Governmental, and programs Facilitation Quantitative, may Affect In a way direct and other direct in performance sector External For this Economies. And I depend Search on Methodology Descriptive - analytical Supported By methods Standard Using Data Panel Data for measurement relationship between Policies expansion and indicators commerce Foreign Ministry with the focus on balance commerce and indicator openness Commercial, to side drawers variables officer like Output Local Total, price Exchange, and rate Inflation. It indicates Results Expected to presence contrast in impact This is amazing Policies between countries Research, where Benefit countries The base Industrial strong like Germany and the Netherlands In a way greater comparison With some countries The other like Italy And Spain, as Reflects openness Commercial level high from integration Economic inside Union European, And get rid of Results to that impact Policies expansion on commerce Foreign Ministry It is characterized Not homogeneity between countries, Which summons coordination greater For policies Economic To ensure stability commercial Sustainable.